Enhancing QOS performance of the 5G network by characterizing mm-wave channel and optimizing interference cancellation scheme / Faizan Qamar - Faizan , Qamar (2019)

(untitled)
With the increase in number of communication devices, the requirement for higher bandwidth is essential. The next generation mobile network is stated as the fifth- generation (5G) and expected to commercialize in the year 2020. Several researchers and mobile operators are working with the third-generation partnership project (3GPP) to achieve higher throughput with greater user capacity. The use of millimeter wave (mm-wave) frequency band is one of the most efficient way to increase the bandwidth because the currently used frequency band (i.e., lower than 6 GHz), is not capable to deliver such high data rate due to the limitation of bandwidth availability. However, utilizing the mm-wave in wireless communication systems has some limitations such as the mm-wave wireless propagated signals are susceptible to blockages by obstacles, shadowing, refraction, diffraction and they are vulnerable to atmospheric absorption and rain attenuation which causes higher propagation path loss. Therefore, in order to practically implement the mm-wave network in the real scenario, the behavior of signal propagation among various channel conditions must be determined. Moreover, the mm-wave network is largely characterized by small cell deployments that cause coverage limitations and interferences issues, due to massive devices are communicating in a small geographical area. Additionally, the implementation of device-to-device (D2D) network in relay node (RN) based small cellular network (also known as D2D enabled cooperative mm-wave cellular network) causes several critical interferences issues such as inter-cell, intra-cell, relay-self, interference from nearby cellular user (CU), RN and D2D users and so on. These issues should be mitigated by using an efficient network designing and interference cancellation schemes. Therefore, this study focuses on designing an interference-free D2D enabled cooperative mm-wave cellular network. The first part of this study is investigating the potential of the mm-wave channel by examining the path loss propagation model such as close-in (CI) and floating-intercept (FI). Initially, the path loss parameters are extracted for 38 GHz frequency band based on real measurements, collected in outdoor urban microcell environments for a line-of-sight (LOS) and non-line-of-sight (NLOS) case and co- and cross-antenna polarizations settings. Subsequently, based on real measurement parameters, the channel performance is evaluated by using several key factors, including cell-edge user throughput, average user throughput, fairness index, average cell throughput, and spectral efficiency for various users capacity. The second part of this study focuses on mitigating the excessive interferences that arises while enabling the D2D network in the above investigated mm-wave network. It introduces a stochastic geometric based Poisson point process (PPP) approach model encompasses base station (BS), RN, CU and D2D users positioning method, aimed to design an interference-free network. The low complex spatial interference cancellation is then applied to model success probability, average capacity and outage probability for the individual network hops. Numerical results proved the robustness of the proposed PPP model against interference as compared with Grid and multi-antenna ultra-dense network (UDN) models. It is believed that the findings presented in the study are useful for designing future interference-free 5G mm-wave communication networks.